Metal-Organic Frameworks (MOFs): A Paradigm Shift in Next-Generation Dental Filling Composites - Khalid Zainulabdeen; Raghda Alasyeed; Hanan Ibrahiem; Amir Hassan; Muna Bufaroosha; Atheel H Alwash; Ahmed Ahmed; Abeer Erfan; Saba Hamza; Rahimi M Yusop; Emad Yousif (Cakradonya Dental Journal, 2026)
Restorative dentistry today faces two main problems that limit the long-term success of dental restorations. Resin-based composites (RBCs) provide better aesthetics than amalgams, they are biologically inert and lack long-term structural durability, often requiring replacement over time. Metal-Organic Frameworks (MOFs) have recently emerged as a new class of crystalline hybrid nanofillers and functional nanomaterials in restorative dentistry. This material comprised of metal ions or clusters linked by organic linkers. This study assesses the potential of MOFs compounds to overcome the key limitations of conventional dental composites. Particular attention is given to their tunable properties, drug-loading capacity, and controlled degradation behavior, especially in biocompatible systems such as Zeolitic Imidazolate Frameworks (ZIFs) and University of Oslo (UiO) frameworks. These characteristics enable sustained antimicrobial release to combat bacterial biofilms, as well as ion release that supports dentin remineralization. In addition, MOFs are evaluated for their role as novel reinforcing fillers, contributing to key mechanical properties such as flexural strength and fracture resistance. Overall, MOFs offer a promising and versatile platform to transform dental composites from purely restorative fillers into durable, biocompatible improved clinical performance.